Globalization and the smallholders: a review of issues, approaches, and implications - Narayanan, Sudha; Gulati, Ashok (International Food Policy Research Institute, 2002)
A major question that has surfaced in the changing context of world agriculture is whether the smallholders would ride the wave of globalization or be swept away. This paper addresses the debate with a four-fold objective: (1) it maps different factors that are likely to impinge on developing country smallholders as a result of globalization in general and of agriculture in particular (2) it briefly reviews literature and summarizes different approaches and methodology used to study this question (3) it identifies areas which have been the focus of attention so far and those that are relatively under-researched (4) it attempts to draw some conclusions regarding the impact of globalization on the smallholders from the literature review, and then suggests some policy implications if globalization is to benefit the smallholders. The paper finds, among others, that studies that focus on trade liberalization alone (operating through price changes) and those that address broader issues of globalization (such as changing structure of food industry and new relationships in the interface of farm and firm, SPS issues, etc.) have run somewhat parallel to each other where a greater integration of the two would be more valuable. Methodological approaches may have something to do with this apparent dichotomy. An important part of this study is to find out from the existing literature whether smallholders have benefited or adversely affected by from the globalization process. There appears to be no clear evidence that smallholders in one region may have done better than those in another. However, even while acknowledging the significant differences within regions themselves, it is evident that whether smallholders have benefited or have been hurt is determined by a fairly narrow range of issues – vertical coordination with processors or exporters, access to infrastructure and finance (credit), role of public sector and international involvement in capacity building, alternatives available in non-farm sector, etc. Based on this, the paper concludes that policy interventions vis-à-vis smallholders should essentially have a twin focus (1) removing the shackles that currently constrain smallholders from exploiting opportunities that globalization presents and (2) ensuring minimum adverse impact, both being two sides of the same coin. While the former can be accomplished through enabling policies, the latter would have to be tackled through coping policies. Particular areas identified as critical enabling factors are greater vertical coordination, removing credit constraints, reducing transactions costs, building social capital, greater role for public sector in providing infrastructure and facilitating institutions and also greater initiatives for international capacity building. On the other hand, coping strategies would include provision of credible safety nets and risk coping instruments, promoting exit options particularly through promotion of opportunities in the rural non-farm sector, guarding against harmful monopolistic competition, and focused research on technologies for small farmers. Needless to say, the relative importance of these factors would vary across regions. It is thus important to identify which battery of policies is appropriate depending on the unique circumstances of each region. It is equally important to draw lessons from the several success stories to be able to replicate these successes on a larger scale in a meaningful way. Only then can small farmers make big gains from globalization.""